A Review Paper on AutomaticSun Tracking System Using on Application of Robotic System - et. al., Jitendra Gupta, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper we will discuss about the Automatic sun tracking system which we will implement on metal detectionaobotic system, where robotic spontaneous sun tracing system is a hybrid hardware/software prototype, whichautomatically furnish best positioningof panelwith the sunlight to get maximal electric charge generation through solar panel. It’s active sensors continuously observed the monochromaticrays of sun and spin the panel about the direction where the potential of sun rays is maximal. A micro-controller works on automatic sun tracing deviceconnected with the new solar power transformunit is developed & execute. The automatic sun tracker is executed with a DC motor and a DC Motor controller. The conditions of the hardware subjected to the changes of the environmental conditions. In the new unit of the MAXIMUM POWER POINT is resolved to easy insertion software with a present sweep perspective, with this new perspective the standardization of the transform from solar energy to electric energy at its maximal power point can be develops extra definitive and extra authentication.